ICON PAINTING OF THE CHURCH IN DRENOVA NEAR LEPOSAVIĆ FROM THE SECOND HALF OF THE 16TH CENTURY (Heritage, 2021)
In the village of Drenova, next to Leposavic, there is a church dedicated to the Annunciation of the Most Holy Mother of God, and it was built during the renewal of the Pec Patriarchate. It is built of hewn stone, small in size and covered with stone slabs. It has a wooden iconostasis made in a modest woodcut and painted with geometric and floral motifs of various colours. The throne icons of Christ and the Mother of God from the iconostasis have not been preserved. The second row of icons is the Seismic Act with the apostles, and above them are the icons of the Great Feast. Due to the small space, part of this repertoire found its place in the middle of the church, on a vertical partition, within the roof construction. The stylistic analysis of painting shows that her master was of modest abilities but excellently trained in his craft. In terms of artistic expression, he is a decorator, whose colour is transparent and not constructive, and he is influenced by Cretan painting. Its palette is modest, composed of only a few saturated tones. As the main colour solutions, he uses harmony performed by the contrast of complementary colours and the collision of light-dark shades. The incarnate works with a certain dose of plasticity, while in draperies this element is extremely emphasized. Linearity matches the colour that carries the form. The characters have anatomical deformations, but they radiate spirituality. The general image of this painting exudes expressiveness, immediacy and cold beauty. Based on the iconographic solutions of the royal doors and their coincidence with the doors of the linotype workshops, it can be concluded that the painter Drenova belonged to one of them. The village of Linotop is located in the area of ​​Kastoria in northern Greece. By analyzing the inscription preserved on the icons, it can be concluded that the painter is of Cincar origin, which corresponds to the geographical determinants. Based on the great similarity of the visual language of iconography in Drenova with the Deisis act in the Piva monastery, this painting can be placed in the last years of the 16th century.
Keywords: Church in Drenova, iconostasis, icons, iconography, style, analogies, linotropic painters.